Os recursos sonoros da música contemporânea como ferramenta criativa no ensino musical - Audrá, Giuliana Cunha Bueno [UNESP] (2014)
Knowing the shortage of artistic and pedagogical proposals involving the teaching of contemporary music in musical education institutions in Brazil I decided set out to accomplish this master thesis. It is a research-action, once worked in a non-hierarchical throughout the research process, with the aim of reshaping, restructuring, interact, engage and reassess a pedagogical practice developed in order to integrate teaching practice, theory and research. The investigation here held describes and analyses the educational activities developed by me and by the composer Sergei Kafejian in the Artistic-pedagogic Project titled Cuiabá Sonora, conducted in 2009, in the city of Cuiabá. The goal of the research was to verify whether pedagogical artistic activities developed there were able to provide participants, further development of musical artistic creativity oriented for listening, performance and creation, and if the course offered contributed to the creation of collaborative compositions entitled: ' plain, three falls and Lake ', ' the fan the bird and the maid ', ' Wall of the echo I and II ' and ' early bird at the big Theatre of erosive River Patience ' listed in the annex. It was also my aim point which sociocultural relations settled in participants groups, due to the adoption of these pedagogical practices and to what extent they were able to assist the personal and musical development of those involved. It was also my intention to verify if these educational resources could be used for other teachers in the teaching of contemporary music. The project lasted for 3 months (12 weeks) and with the participation of all students from the „ponto de cultura’ ' Project Ciranda-music and citizenship '. In it were developed some creative musical practices inspired by the educational proposals of Murray Schafer and John Paynter. Were also used musical creations procedures present in contemporary...